Taxonomic revision of Anicius Chamberlin, 1925 (Araneae: Salticidae), with five new species of jumping spiders from Mexico - Guerrero-Fuentes, Dariana R.; Francke, Oscar F. (Zootaxa, 2019)
Anicius Chamberlin, 1925 is a monotypic genus and only the male of A. dolius Chamberlin, 1925 has been described. Herein the genus is revised and the female of the type species is described for the first time; new distribution records are also provided for this species. Five new species from Mexico are described based on males and females: Anicius chiapanecus sp. nov., Anicius cielito sp. nov., Anicius faunus sp. nov., Anicius grisae sp. nov., and Anicius maddisoni sp. nov. A key for identification of males and females is given, as well as a map with distribution records of the six species.